(untitled) (Annals of Medical Research, 2022)
Aim: We investigate whether the systemic immune-inflammation index (SII), an easily evaluated inflammatory and immune response marker, is associated with the SYNTAX score (SS) in patients admitted with suspected CAD who underwent coronary angiography (CAG). Materials and Methods: Evaluated retrospectively were 456 patients who underwent CAG in the cardiology outpatient clinic between January 2020 and January 2022. The SII was calculated by the following formula: neutrophils × platelets / lymphocytes. SS values were divided into 3 groups; low group (<22), intermediate group (22-32) and, high group (≥32). Those with SS values of 0 were taken as the control group. Results: The median SII value was higher in the CAD group compared to the control group (631.0 vs. 381.5, p<0.001) and a positive correlation was found between the SS and SII (r=0.578, p<0.001). Median SII values increased from the low SS group to the high SS group (p<0.05 for each SS group). The cut-off value of the SII in predicting the presence of CAD was >594.2, with 56.7% sensitivity and 91.1% specificity (AUC±SE: 0.807±0.020, p<0.001). In addition, it was found that the SII predicted low SS compared to the control group (OR=1.06; p<0.001), intermediate SS compared to the low SS group (OR=1.03; p<0.001), and high SS compared to the intermediate SS group (OR=1.04; p<0.001). Conclusion: The SII has the potential to be a screening marker for the presence and severity of CAD before CAG. This study demonstrates that the SII is independently associated with coronary atherosclerosis burden.